PENGARUH BAHAN BAKU DAN PEREKAT UREA-FORMALDEHIDA TERHADAP SIFAT-SIFAT PAPAN SERAT - Rena M Siagian; Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1988)
Properties  of hardboard are not  only  effected by the raw material used and the basic manufacturing process employed but  influenced   by subsequent processing  of  treatment such as gluing,  impregnation, heat  treatment  and oil tempering. The purpose  of  the  research is to study   the  effect   of  raw material  and  urea-formaldehyde    adhe11ive  on hardboard  properties. The  raw  material comprise   of  yute (Corchorus capsularis L),  rosella  (Hibiscus  sabdariffae L),   kena; (H.  cannabinus), linum  (Linum  usitatissimum L), dan lamtorogung (Leucaena leucocephalla). The level of  the urea-formaldehyde adhesive incooperated   in the experiment  were  0 and 1.5 per  cent  based on  oven dry  pulp.The  results  indicate   that  the  raw material used for  hardboard  making  has a significant  effect on pulp  yield,  alkali consumption,  water  absorption,   tensile  strength  parallel  to surface,  and  modulus  of  rupture.   Tensile   strength  parallel  to surface  of  hardboard  was significantly   effected  by adding  urea-formaldehyde adhesive.  The  hardboard  made  of kenaf has the highest  tensile strength  parallel to surface,  and modulus  of rupture,  and high water absorption. For decreasing the latest properties, perhaps  phenol  formaldehyde.  can  be added  to  the stock.